Designing a Web-Based Digital Financial System for Islamic Boarding Schools with Payment Gateway Integration - Ahmad Hudawi; Nor Jaykiah; Ummi Lailatul Firdausi (Universitas Nurul Jadid, 2025)
Financial management in Islamic boarding schools still faces various fundamental problems, particularly due to dependence on manual recording and simple applications. This management pattern often causes delays in report preparation, increases the potential for recording errors, and reduces transparency. This condition impacts the trust of students' guardians and stakeholders. In addition, the diversity of student guardians, including those from outside the region, further complicates the payment process due to limited access to remote transaction services. This situation highlights the urgency of developing a web-based digital financial system that can effectively integrate modern payment technology and adapt to the needs of Islamic boarding schools. This study aims to design and implement a digital financial system for Islamic boarding schools by integrating the Midtrans payment gateway to improve financial management's efficiency, transparency, and accountability. The method used is a model consisting of three main stages: data collection through observation and interviews with financial managers, system design using use case diagrams, activity diagrams, and class diagrams, and system testing with internal and external black box testing approaches. The system implementation utilizes the Laravel framework, MySQL database, and web-based interface with Login, Dashboard, student data, payment, and financial reporting features. The results show that the developed System can comprehensively address the financial management needs of Islamic boarding schools. External testing using a Likert scale questionnaire obtained a rating of Good-Very Good with an achievement of up to 86%, thus confirming the feasibility of the system implementation. This System has been proven to facilitate online payments, accelerate the report preparation process, and improve access to information for student guardians. Thus, a web-based digital financial system integrated with a payment gateway can be a strategic solution for enhancing the transparency and accountability of pesantren finances. Further research is recommended to strengthen data security, expand coverage to multiple pesantren, and conduct continuous testing on a broader scale